Slum Area Management in Asahan Regency - Saputri, Welda; Nuraini, Cut (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to examine the management of slum areas in Asahan Regency. The study uses a qualitative approach supported by quantitative data to gain a deeper understanding of slum area management in Asahan Regency. The reliability of the data obtained will be compared through triangulation techniques, ensuring the consistency of findings from various sources and data collection methods. The researcher will conduct member checking by confirming with several respondents to ensure that the interpretation of the interview results aligns with the respondents' intentions. The results show that active community involvement in the planning and implementation of management programs is crucial to creating a sense of ownership and responsibility. The develop-ent and improvement of basic infrastructure, such as roads, drainage systems, and clean water supply, have had a positive impact on the health and well-being of the community. Economic empowerment programs targeting the residents of slum areas have proven to be an important solution for improving welfare. Despite various challenges, limited resources remain one of the biggest obstacles in slum area management. Overall, slum area management in Asahan Regency requires a comprehensive and sustainable approach, involving all stakeholders.